2021
DOI: 10.3389/fneur.2021.651635
|View full text |Cite
|
Sign up to set email alerts
|

Trigonal-Sparing vs. Trigonal-Involved OnabotulinumtoxinA Injection for the Treatment of Overactive Bladder: A Systematic Review and Meta-Analysis

Abstract: Objective: Overactive bladder (OAB) is a disease characterized by the presence of urinary urgency. We carried out a meta-analysis to assess the effectiveness and safety of trigonal-involved injection of onabotulinumtoxinA (BoNT-A) in comparison with the trigonal-sparing technique in cases with OAB [neurogenic detrusor overactivity (NDO) and idiopathic detrusor overactivity (IDO)].Methods: Randomized controlled trials (RCTs) of BoNT-A injection for OAB were searched systematically by using EMBASE, MEDLINE, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Three high-quality meta-analyses assert that trigone injection is not only safe but potentially more effective than trigone-sparing technique. 6,8,9 As outlined in the results we note that many of the studies are of small sample size and are lacking in consistent follow-up or methodology regarding efficacy and adverse effects.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Three high-quality meta-analyses assert that trigone injection is not only safe but potentially more effective than trigone-sparing technique. 6,8,9 As outlined in the results we note that many of the studies are of small sample size and are lacking in consistent follow-up or methodology regarding efficacy and adverse effects.…”
Section: Discussionmentioning
confidence: 87%
“…Cui et al's 9 meta‐analysis evaluated the effectiveness and safety of BTN/A injections for iOAB and nOAB. The analysis included six trials with total 437 patients and showed that injections including the trigone were more effective than trigone‐sparing injections in improving symptoms, achieving dryness, reducing frequency of incontinence, decreasing detrusor pressure, and increasing voiding volume.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The large proportion of patients refractory to pharmacotherapy also supports an alternative pathophysiology to detrusor overactivity seen in OAB. Indeed, the relative success of neurotoxins that inhibit sensory nerve activity, such as resiniferatoxin and BOTOX ( Guo et al, 2013 ; Hsieh et al, 2016 ; Cui et al, 2021 ), in relieving OAB symptoms refractory to pharmacotherapy suggests increased sensory outflow is responsible for the symptoms of urgency and urinary frequency. However, BOTOX treatment is invasive, has been associated with frequent side effects, and requires repeated doses at approximately 6 months intervals ( Schurch et al, 2005 ; Apostolidis et al, 2009 ; Chen and Kuo, 2020 ) indicating the treatment is masking, rather than treating the underlying cause of bladder sensory neuron hypersensitivity.…”
Section: Diagnosis Treatment and Pathophysiology Of Overactive Bladdermentioning
confidence: 99%